From inside the cabin: Truck drivers' technology acceptance of driving assistance systems - Tim Gruchmann; Wolfgang Grenzfurtner; Axel Salzmann (Logistics Research, 2024)
Driving assistants offer opportunities for innovation in transportation logistics by preventing accidents and improving workers' well-being. The related transition towards technological interaction, however, changes the spectrum of job tasks and the drivers' perceptions of their workplace. In this vein, driving assistants are not always viewed positively and deactivated. Using a quantitative research approach of conducting online surveys among truck drivers in Germany (N=142), a theoretical framework based on the Technology Acceptance Model and Innovation Diffusion Theory is tested with PLS-SEM and mediation analyses. As a result, the use of assistance systems and its acceptance is mainly driven by social norms, functionality, and trialability. The research contributes to the behavioral operations management discourse concerned by studying of how behavioral factors, such as cognitive biases and social preferences, influence and impede the interaction with assistance systems. Managerial and policy recommendations are further provided for improving the job design in transport logistics and related incentives for advanced use.
Keywords: 650; Behavioral operations management; Driving assistance; Technology acceptance model; Innovation diffusion theory; PLS-SEM